Graphene quantum dots induce apoptosis, autophagy, and inflammatory response via p38 mitogen-activated protein kinase and nuclear factor-κB mediated signaling pathways in activated THP-1 macrophages. (2nd January 2015) - Qin, Yiru; Zhou, Zhi-Wei; Pan, Shu-Ting; He, Zhi-Xu; Zhang, Xueji; Qiu, Jia-Xuan; Duan, Wei; Yang, Tianxin; Zhou, Shu-Feng
Abstract: The biomedical application of graphene quantum dots (GQDs) is a new emerging area. However, their safety data are still in scarcity to date. Particularly, the effect of GQDs on the immune system remains unknown. This study aimed to elucidate the interaction of GQDs with macrophages and the underlying mechanisms. Our results showed that GQDs slightly affected the cell viability and membrane integrity of macrophages, whereas GQDs significantly increased reactive oxygen species (ROS) generation and apoptotic and autophagic cell death with an increase in the expression level of Bax, Bad, caspase 3, caspase 9, beclin 1, and LC3-I/II and a decrease in that of Bcl-2. Furthermore, low concentrations of GQDs significantly increased the expression of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-8, whereas high concentrations of GQDs elicited opposite effects on the cytokines production. SB202190, a selective inhibitor of p38 mitogen-activated protein kinase (MAPK), abolished the cytokine-inducing effect of GQDs in macrophages. Moreover, GQDs significantly increased the phosphorylation of p38 MAPK and p65, and promoted the nuclear translocation of nuclear factor-κB (NF-κB). Taken together, these results show that GQDs induce ROS generation, apoptosis, autophagy, and inflammatory response via p38MAPK and NF-κB mediated signaling pathways in THP-1 activated macrophages.